2018
DOI: 10.33043/jsacp.5.3.70-94
|View full text |Cite
|
Sign up to set email alerts
|

Power Politics: Advocacy to Activism in Social Justice Counseling

Abstract: The authors seek to initiate a broader dialog within the social justice movements across disciplines to include a deeper understanding of how power politics plays out in the social/political domain of the public arena outlined in the American Counseling Association (ACA) Advocacy Competencies. In this domain, counselors act as legislative/policy change advocates. However, in recent years social justice advocates within the profession have called for a more activist stance focusing on changing social structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 53 publications
0
21
0
1
Order By: Relevance
“…Others agreed (e.g., Chung & Bemak, 2012;Goodman et al, 2004;C. C. Lee & Hipolito-Delgado, 2007;M. A. Lee, Smith, & Henry, 2013), and the revised Multicultural and Social Justice Competencies were endorsed by American Counseling Association Governing Counseling in 2015 (Ratts et al, 2016).…”
Section: Social Justice: the Fifth Forcementioning
confidence: 99%
See 1 more Smart Citation
“…Others agreed (e.g., Chung & Bemak, 2012;Goodman et al, 2004;C. C. Lee & Hipolito-Delgado, 2007;M. A. Lee, Smith, & Henry, 2013), and the revised Multicultural and Social Justice Competencies were endorsed by American Counseling Association Governing Counseling in 2015 (Ratts et al, 2016).…”
Section: Social Justice: the Fifth Forcementioning
confidence: 99%
“…It is distinct from traditional models of psychotherapy in that the etiology of mental illness is viewed as rooted in social dysfunction rather than as primarily due to internal personal deficits or narratives. This assumption requires knowledge and understanding of the politics of power, including the oppressive power of injustice and the liberating power of social justice (Albee & Joffe, 2004;M. A. Lee et al, 2013;McWhirter, 1997;Prilleltensky, 2008Prilleltensky, , 2012bPrilleltensky, , 2013Williams & Barber, 2004).…”
Section: Social Justice: the Fifth Forcementioning
confidence: 99%
“…To do so, it would require an active and responsible participation not only from counselors but also from the people, groups, and family systems to whom the advocacy intervention is directed, as an integral part of the counseling process. According to this approach, the philosophy of counseling intervention includes a kind of social action that aims at uprooting elements of unfairness (Lee & Walz, 1998) and this becomes an important goal and object of the overall counseling process (Lee, Smith & Ryan, 2013).…”
Section: Counseling Philosophy In Italymentioning
confidence: 99%
“…Suggesting otherwise neglects the precariousness facing individuals that depend on institutions with ready-made habits, flows, and wills for survival. Lee et al (2013) noted the challenges facing professionals who take on well-defended power structures including burnout, sacrificing personal life, jeopardizing professional standing, and being labeled a troublemaker, not to mention that this labor is not compensated. Similarly, Flood et al (2013) pointed to several challenges facing academics specifically including attacks, threats to security and advancement, and isolation by peers.…”
Section: The Case Of Academic Psychologymentioning
confidence: 99%
“…Echoing the work of Speer (2008), for example, Lee et al (2013) concluded that “relying on elite sources of power . .…”
Section: Habitual Change In Counseling Psychologymentioning
confidence: 99%